2016
DOI: 10.1063/1.4958890
|View full text |Cite
|
Sign up to set email alerts
|

Properties of slow traps of ALD Al2O3/GeOx/Ge nMOSFETs with plasma post oxidation

Abstract: The realization of Ge gate stacks with a small amount of slow trap density as well as thin equivalent oxide thickness and low interface state density (Dit) is a crucial issue for Ge CMOS. In this study, we examine the properties of slow traps, particularly the location of slow traps, of Al2O3/GeOx/n-Ge and HfO2/Al2O3/GeOx/n-Ge MOS interfaces with changing the process and structural parameters, formed by atomic layer deposition (ALD) of Al2O3 and HfO2/Al2O3 combined with plasma post oxidation. It is found that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 27 publications
3
14
0
Order By: Relevance
“…22 This result suggests that the location of slow traps is close to the GeO x /Ge interfaces for n-Ge MOS interfaces, as concluded for the post-PO Al 2 O 3 /GeO x /n-Ge MOS structures. 22 On the other hand, it is found in Figure 4d that the Al 2 O 3 /GeO x /p-Ge gate stacks with a significant GeO x thickness leads to a lower ΔN st and that thinner GeO x leads to higher ΔN st at a given E ox . This result means that the areal slow trap density decreases with an increase in the GeO x thickness, which can be interpreted by considering that the main slow traps for holes exist close to the Al 2 O 3 /GeO x interfaces.…”
Section: Resultssupporting
confidence: 67%
See 4 more Smart Citations
“…22 This result suggests that the location of slow traps is close to the GeO x /Ge interfaces for n-Ge MOS interfaces, as concluded for the post-PO Al 2 O 3 /GeO x /n-Ge MOS structures. 22 On the other hand, it is found in Figure 4d that the Al 2 O 3 /GeO x /p-Ge gate stacks with a significant GeO x thickness leads to a lower ΔN st and that thinner GeO x leads to higher ΔN st at a given E ox . This result means that the areal slow trap density decreases with an increase in the GeO x thickness, which can be interpreted by considering that the main slow traps for holes exist close to the Al 2 O 3 /GeO x interfaces.…”
Section: Resultssupporting
confidence: 67%
“…We have also reported the slow trap behavior of ALD Al 2 O 3 /GeO x /n-Ge MOS interfaces formed by post-PO and n-channel MOSFETs using these MOS interfaces. 22 Effective slow trap density at the Ge MOS interfaces and the time constant of the source current in Ge n-MOSFETs do not significantly change with varying the thickness of Al 2 O 3 and GeO x , which has been demonstrated. These results have indicated that the main slow traps for electrons exist inside the GeO x /Ge control layers.…”
Section: Introductionmentioning
confidence: 69%
See 3 more Smart Citations